2011
DOI: 10.1093/hmg/ddr208
|View full text |Cite
|
Sign up to set email alerts
|

Identification and functional characterization of rare mutations of the neuroligin-2 gene ( NLGN2 ) associated with schizophrenia

Abstract: Schizophrenia is a severe chronic mental disorder with a high genetic component in its etiology. Several lines of study have suggested that synaptic dysfunction may underlie the pathogenesis of schizophrenia. Neuroligin proteins function as cell-adhesion molecules at post-synaptic membrane and play critical roles in synaptogenesis and synaptic maturation. In this study, we systemically sequenced all the exons and promoter region of neuroligin-2 (NLGN2) gene in a sample of 584 schizophrenia patients and 549 con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
107
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 124 publications
(116 citation statements)
references
References 36 publications
7
107
0
2
Order By: Relevance
“…There is increasing interest in the neuroligin family in schizophrenia because neuroligins form transsynaptic complexes with schizophreniaassociated neurexin (NRX) proteins (61,62). NLGN-NRX complexes are known to be important in brain development, and genetic variation in these genes has been associated with autism and schizophrenia (63)(64)(65)(66). The NLGN1-NRX complex has been found to specifically localize to glutamatergic synapses, where it helps stabilize the synapse and recruit additional synaptic proteins involved in synapse structure and function.…”
Section: Resultsmentioning
confidence: 99%
“…There is increasing interest in the neuroligin family in schizophrenia because neuroligins form transsynaptic complexes with schizophreniaassociated neurexin (NRX) proteins (61,62). NLGN-NRX complexes are known to be important in brain development, and genetic variation in these genes has been associated with autism and schizophrenia (63)(64)(65)(66). The NLGN1-NRX complex has been found to specifically localize to glutamatergic synapses, where it helps stabilize the synapse and recruit additional synaptic proteins involved in synapse structure and function.…”
Section: Resultsmentioning
confidence: 99%
“…3), providing an important research tool for future studies on different subtypes of receptors. Furthermore, we have recently demonstrated that such a model system is useful for the screening of human disease-related gene mutations by co-expressing GABA A -Rs with wild type or mutant NL2 identified from patients with schizophrenia (62). Our previous and current studies suggest that molecularly engineered hetero-synapses are a versatile model system that can be used to study not only synaptogenesis but also receptor targeting and functional deficits of gene mutations.…”
Section: Discussionmentioning
confidence: 86%
“…Difference in the expression levels of specific KCC2 transcripts has been linked to schizophrenia and affective disorders (38). We have previously discovered a significant decrease of KCC2 expression induced by a neuroligin 2 mutation found in patients with schizophrenia (39,40), suggesting a potential role of KCC2 in the pathogenesis of schizophrenia. Altered KCC2 expression has also been implied in stress (41).…”
Section: Discussionmentioning
confidence: 98%